Web-Based Patient Referral System Design from Clinic to Hospital Using Object Oriented Programming System - Yunianto Agung Nugroho; Riyanto Riyanto; Joni Iskandar; Mustar Aman; Nuri Wiyono (Universitas Bina Darma, 2023)
The clinic in Tangerang Regency, Indonesia is a healthcare institution where people seek treatment and medical advice. However, the patient referral system to the hospital in the polyclinic still uses the old method, which involves a letter of introduction from the clinic, a conventional way of documenting the chronology of the patient's illness and using a certificate or cover letter at the clinic. Patient data with problems going to the hospital is not stored in the database, and as a result, patients may have to postpone going to the hospital. The purpose of this study is to determine the current patient referral system from clinics to hospitals and design a web-based patient referral information system that can integrate patient data into the hospital. This research uses a descriptive qualitative method to analyze and design the system, employing the Object-Oriented System Design method. The output of this research is software, which is a web-based patient referral information system that displays completed patient data and disease chronology accurately and quickly, supporting digital concepts.